The Effect of Smart Parenting Training on Increasing Parental Self-Efficacy of Working Mothers with Toddlers - Mirna Ayu Irpadila; Eva Meizara Puspita Dewi; Dian Novita Siswanti (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
Parental self-efficacy is an important predictor that influences the positive behavior of parents in parenting. This study aims to determine the effect of smart parenting training on increasing parental self-efficacy of working mothers with toddlers. This study used a quasi-experimental design with the untreated control group design with dependent pretest and posttest samples. A total of 14 participants were divided into two groups, namely seven participants in the experimental group and seven participants in the control group. Smart parenting training uses experiential learning models and e-learning video-based methods. Measurements in this study used a short version of the Self-efficacy for Parenting Tasks Index-Toddler Scale (SEPTI-TS). The results of data analysis using the Mann-Whitney U show that there is a significant difference in parental self-efficacy (ρ=0.002) in the experimental group and the control group, and based on the Wilcoxon sign rank test shows that there is an increase in parental self-efficacy in the experimental group (ρ=0.018) after receiving smart parenting training, whereas in the control group participants (ρ=0.680) there was no increase in parental self-efficacy. The results showed that smart parenting training affected increasing parental self-efficacy for working mothers with toddlers.